2D unified atmosphere and wind simulations for a grid of O-type stars - Moens, Nicolas; Debnath, D.; Verhamme, O.; Backs, F.; Sijpt, C. Van der; Sundqvist, J. O.; Sander, Andreas A. C. (Astronomy and astrophysics, 2025)
Context. The atmospheres of massive O-type stars (O stars) are dynamic, turbulent environments resulting from radiatively driven instabilities over the iron bump, located slightly beneath the stellar surface. Here, complex radiation hydrodynamic processes affect the structure of the atmosphere as well as the formation of spectral lines. In quantitative spectroscopic analysis, the effects of these processes are often parametrized with ad hoc techniques and values. Aims. This work is aimed at exploring how variation of basic atmospheric parameters affects the dynamics within the subsurface turbulent zone. We also explore how this turbulence relates to absorption lines formed in the photosphere for a broad range of O stars at solar metallically. Methods. The work in this paper centers around a grid of 2D, radiation-hydrodynamic O-star atmosphere and wind simulations, where the turbulent region is an emergent property of the simulation. For each of the 36 models in the grid, we derived the turbulent properties and correlated them to an estimate of turbulent line broadening imposed by the models’ velocity fields. Results. Our work suggests that the subphotospheric turbulent velocity in O-stars scales approximately with the square of the Eddington parameter, Γe. We also find a linear correlation between subphotospheric turbulent velocity and the line broadening of several synthetic photospheric absorption lines. Radiation carries more energy than advection throughout the atmosphere for all models in the grid; however, for O-type supergiants, the latter can account for up to 30 % of the total flux at the peak of the iron bump.